Temperature dependence of the electrical characteristics up to 370 K of amorphous In-Ga-ZnO thin film transistors. (January 2016) - Estrada, M.; Rivas, M.; Garduño, I.; Avila-Herrera, F.; Cerdeira, A.; Pavanello, M.; Mejia, I.; Quevedo-Lopez, M.A.
Abstract: The temperature dependence in the typical temperature operating range from 300 K up to 370 K of the electrical characteristics of IGZO TFTs fabricated at temperatures not exceeding 200 °C is presented and modeled. It is seen that up to T  = 330 K, the transfer curves show a parallel shift toward more negative voltages. In both subthreshold and above threshold regimes, the drain current shows Arrhenius-type dependence. In the latter case, for low temperatures, the activation energy is around 0.35 eV for VGS  = 10 V, reducing as VGS is increased. The observed behavior is consistent with having the VRH transport mechanism as the predominant one in conduction. Graphical abstract: Highlights: We study Indium–Gallium–Zinc Oxide transistors with temperature. An Arrhenius-type dependence is seen in the temperature range from 300 K up to 370 K. The predominant transport mechanism observed is the Variable Range Hopping. Modeled characteristics at different temperatures matches well the experimental ones.